The ballade plot about the soldier coming back: textualization and transformation of the motive pool - Hulak, Nastassia A. (Journal of the Belarusian State University. Philology, 2019)
In a broad folkloristic context, the article analyzes a late traditional ballade plot The husband comes unrecognized from war. Based on the ХІХ–ХХ centuries publications, the work demonstrates the plot’s main relevant forms. The original plot variant used by the Belarus partisans of the Great Patriotic War are introduced into scientific discourse for the first time. The article proves the plot’s connection to the ballade tradition and explores its productive realization in the genre of a soldier’s song. It is proved that the plot employs five motives that embody semantic universals of the traditional culture and form a sustainable problem-thematic field. The article states that the plot tradition in its development aims at reducingits lyrico-epic component and increasing its narrative expression.
Keywords: folklore studies; narrative tradition; textualization of a motive; soldier’s song; motive pool; ballade